Reflections on public-private participation in healthcare - Regina RP Carvalho; Paulo AC Fortes; Volnei Garrafa (Instituto Nacional de Salud Pública, 2014)
Health care is one of the major issues in social policy, affected by multiple factors, such as the increase in health costs, crisis, and the degree of private participation in the financing of services. In this essay we reflect on this participation of the private sector in health care, with Brazil as a reference country and taking into account member states of the Union of South American Nations. Based on a qualitative study using data from national and international organizations, we found significant private participation in health care of countries in various continents, with an increase of public and private spending between 2000 and 2010. Regardless of the adopted health system, there was an increase of private spending in most countries analyzed, which emphasizes the need to further evaluate the performance of public and private sectors, as well as the regulatory frameworks for their participation in health care, thus enabling policies that promote quality improvement and the expansion of coverage.